An epidemiological survey of anhidrotic/hypohidrotic ectodermal dysplasia in Japan: High prevalence of allergic diseases. Issue 4 (13th December 2021) - Inazawa‐Terada, Minako; Namiki, Takeshi; Omigawa, Chika; Fujimoto, Tomoko; Munetsugu, Takichi; Ugajin, Tsukasa; Shimomura, Yutaka; Ohshima, Yuichiro; Yoshida, Kazue; Niizeki, Hironori; Hayashi, Ryota; Nakano, Hajime; et al.
Abstract: Anhidrotic/hypohidrotic ectodermal dysplasia (A/HED) is a congenital disorder characterized by anhidrosis/hypohidrosis and inadequate hair and dental dysplasia. Large‐scale case studies of patients with A/HED have already been conducted overseas, while there has been no large‐scale study, but only a few case reports in Japan. Furthermore, an epidemiological study of this disease has not been conducted in Japan to date. The purpose of this study was to investigate the clinical characteristics of A/HED patients, the status of genetic aberrations and complications of A/HED in Japan. Initially, we conducted a physician‐initiated questionnaire survey of A/HED patients who visited medical institutions across Japan to investigate their backgrounds, clinical symptoms, genotypes, diagnostic methods and complications of A/HED. We also investigated the presence or absence of various allergic diseases (atopic dermatitis‐like skin manifestations, bronchial asthma and food allergies). Questionnaires were also obtained from 26 patients with ectodermal dysplasia (ED) who visited four medical institutions. We compared the incidence of allergic diseases in healthy controls in a similar study to that of patients. Twenty‐four of those patients were considered to have A/HED, of which 18 had a confirmed genetic diagnosis and were genotyped. All patients had anhidrosis or hypohidrosis, hair and dental dysplasia, and unique facial appearance; 23 patients had several cutaneous manifestations and seven patients had periorbital pigmentation. In addition, there was a significantly higher incidence of atopic dermatitis‐like cutaneous manifestations, bronchial asthma and food allergies in the A/HED patients than in healthy controls. We report the results from a questionnaire survey of 24 patients with A/HED. This is the first report of a large number of A/HED patients in Japan. This study clarifies the status of clinical diagnosis and genetic testing of A/HED patients in Japan, as well as the characteristics of their skin symptoms and allergic complications.